The Assessment of Forensic Disguising Markers for Food Poisoning and their Control Measures. A Health Awareness Study - Javed Iqbal Khokhar, Muhammad Ikram Ali, Rizwana Hussain, Sadaf Nadir, Tufail Ahmed Soomro, Arslan Shuja (Pakistan Journal of Medical & Health Sciences, 2022)
Aims and objectives: To uncover the disguising markers of food poising and their Control Measures to spread public awareness for betterment of human health through forensic applications. Materials and Methods: Study design: Present study was conducted from December 2021to June 2022 in Lahore. Sample size and collections: Various food samples were collected from 10 different restaurants. 5 different food products were collected from each restaurant for analysis of biological markers while non-biological markers were observed on the location at a data collection Performa. Chemical analysis: In case of food poising the forensic chemical analysis are based on biochemical and physiological tests such as bacterial Count in collected food samples through plate count method and spectrophotometric (turbid metric) analysis. Determined Parameters: In this study both biological parameters, such as bacterial Count and non-biological parameters like, hygiene, quality of water, utensils quality, cooking style and cooking environment were considered. Results presentations: Raw data of each parameter was represented bio-statistically with the applications of SPSS in which regressions of standard mean deviation and significant (P<0.05) were considered comparatively. Results: It has seen that mostly all food samples taken from different restaurants have bacterial flora. These bacterial count may be so harmful for human life. It was concluded by considering non-biological parameters that the hygienic conditions, cooking place and way of cooking were not according to the standard health levels recommended by food authority. Especially quality of raw material and utensils were not standardized. All the results were significant as compared with the given standard levels of each parameter. A remarkable changes were noted in different parameters regarding food quality for further elaboration results are represented graphically in fig-1. Conclusion: Infectious organisms including bacteria, viruses and parasites or their toxins are the most common causes of food poisoning. Infectious organisms or their toxins can contaminate food at any point of processing or production. Contamination can also occur at home if food is incorrectly handled or cooked.